The Influence of Product Design and Business Location on Competitive Advantage at Sinar Jaya Lahat Furniture Store - Aam Maryamah; Darwin Kesuma; Heri Fitriadi (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study is to determine the effect of product design on competitive advantage at Sinar Jaya Furniture Store in Lahat. To determine the effect of business location on competitive advantage at Sinar Jaya Furniture Store in Lahat. To determine the effect of product design and business location on competitive advantage at Sinar Jaya Furniture Store in Lahat. The sample in this study consisted of 71 consumers at Sinar Jaya Furniture Store in Lahat. The analysis and calculations show that product design significantly influences competitive advantage at Sinar Jaya Furniture Store in Lahat. Business location significantly influences competitive advantage at Sinar Jaya Furniture Store in Lahat. Product design and business location significantly influence competitive advantage at Sinar Jaya Furniture Store in Lahat.